El derecho al desarrollo en el 60 aniversario de la Declaración Universal de los Derechos Humanos: estado de la cuestión - Angulo Sánchez , Nicolás (Nómadas. Critical Journal of Social and Juridical Sciences, 2009)
The right to development is a human right that includes the ensemble of human rights and shows the universality, interdependence and indivisibility of such rights, but the globalization which is being imposed nowadays is characterized by a vision of human reality that is essentially individualistic and commercial, with no concern for the dramatic current economic and social inequalities, and what’s worse, aggravating them and making them even deeper.